Effect of binahong leaf extract on the growth of Candida albicans in patients using removable orthodontic appliances - Renate Vania De Leilus Homans; Donald R. Nahusona (Makassar Dental Journal, 2020)
Background: In the oral cavity there are countless microorganisms, about 40% of which are Candida albicans as normal flora. The use of removable orthodontic appliances in the oral cavity greatly inhibits cleanliness and increases the number of retentive areas in the oral cavity resulting in risk factors of increased C.albicans. Binahong leaves contain many active compounds that are antimicrobial. Objective: To determine the effect of binahong leaf extract in inhibiting the growth of C.albicans in patients using removable orthodontic appliances. Method: Laboratory experimental research was conducted with the design of the posttest only control group design involving 5 samples of removable orthodontic appliances which were swabbed to obtain C.albicans, then each tested with binahong leaf extract concentrations of 10%, 30%, 50%, 70% and the control group. Next is the inhibitory test. Results: The greater concentration of the Binahong leaf extract, the greater the diameter of the resistance. Conclusion: Binahong leaf extract has an effect on inhibiting the growth of C.albicans in patients using removable orthodontic appliances.